2020
DOI: 10.1055/a-1056-3148
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Improves the Implantation Rate in Patients with Elevated Th1/2 Helper Cell Ratio and Repeated Implantation Failure (RIF)

Abstract: Introduction An abnormal endometrial immune response is involved in the pathogenesis of repeated implantation failure (RIF), so we investigated the effectiveness of tacrolimus treatment on the endometrium of RIF patients. Materials and Methods Ten RIF patients with elevated T-helper 1/T-helper 2 (Th1/Th2) cell ratios were recruited into a clinical study. The expression of p53, leukemia inhibitory factor (LIF), interleukin (IL)-4, IL-10, IL-17, and interferon gamma (IFN-γ) in the endometrium of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…A lower proportion of uNK cells was detected in combination with up‐regulation of leukemia‐inhibiting factor (LIF), interleukin (IL)‐10, and IL‐17 in the cohort with tacrolimus treatment, resulting in an implantation rate of 40%. The quantity of uNK cells in the well‐defined and dated endometrium in the present study may therefore provide evidence regarding subfertility in patients 8 …”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…A lower proportion of uNK cells was detected in combination with up‐regulation of leukemia‐inhibiting factor (LIF), interleukin (IL)‐10, and IL‐17 in the cohort with tacrolimus treatment, resulting in an implantation rate of 40%. The quantity of uNK cells in the well‐defined and dated endometrium in the present study may therefore provide evidence regarding subfertility in patients 8 …”
Section: Introductionmentioning
confidence: 62%
“…The quantity of uNK cells in the well-defined and dated endometrium in the present study may therefore provide evidence regarding subfertility in patients. 8 King et al reported that natural killer (NK) cells are closely associated with trophoblast invasion. The physical proximity of uNK cells to trophoblasts, their precise up-regulation in density around the time of implantation, and their ability to release cytokines known to stimulate trophoblast development 2,9 all point to a key role of uNK cells in early pregnancy events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LIF, IL-10, and IL-17 expression were upregulated and IL-4, IFN-γ expression, and IFN-γ/IL-10 ratio were downregulated post-treatment. Moreover, rate of implantation, clinical pregnancy, and live birth were 40, 50, and 35% respectively, in RIF women without a history of previous successful pregnancy [219]. Considering the results of these studies, Th1/Th2 ratio may be a biomarker for predicting ART outcomes in RIF patients and selection of suitable candidates for tacrolimus administration.…”
Section: Tacrolimusmentioning
confidence: 91%
“…We have previously shown that the use of a low-dose (0.1 mg/kg) tacrolimus (formerly known as FK506; a 822 kDa naturally occurring lipophilic macrolide lactone immunosuppressant that was first isolated from the soil bacterium Streptomyces tsukabaensis [ 19 ] restores placentation and prevents uterine SAR defects in a murine model of FGR and recurrent implantation failure [ 20 ]. Recently, tacrolimus has also been used to treat female infertility and prevent adverse pregnancy outcomes in women with recurrent pregnancy loss with elevated systemic Th1 (CD4+ IFNγ+): Th2 (CD4+IL4+) cell ratios [ 21 , 22 , 23 ]. The well-characterized mode of action of tacrolimus is the inhibition Ca ++ dependent activation of NFκB and the nuclear factor of activated T cells (NFAT) in T lymphocytes blocking T-cell receptor-mediated lymphokine gene transcription, degranulation, exocytosis and apoptosis [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%